Arterial percutaneous angioplasty in hemodialysis access: Endovascular treatment of hand ischemia. Issue 3 (May 2021) - Teixeira, Gabriela; Almeida, Paulo; Loureiro, Luís; Antunes, Inês; Rego, Duarte; Teixeira, Sérgio; Mendes, Daniel; Sousa, Clemente N; Queirós, José; de Matos, Norton; Almeida, Rui
Background: Hemodialysis access–induced distal ischemia consists of symptomatic extremity malperfusion after vascular access creation. It is usually caused by discordant vascular resistance, with arteriovenous shunting of a high blood volume from arterial into venous system and subsequent hand hypoperfusion. Less often, hemodialysis access–induced distal ischemia is caused by arterial stenosis. In these cases, access frequently has normal/low flow, radial pulse is usually absent and not recoverable with vascular access digital compression, diabetes is often present, and percutaneous transluminal angioplasty can be critical for access and limb salvage. Methods: Retrospective study conducted between June 2011 and February 2018 of patients with vascular access submitted to arterial percutaneous transluminal angioplasty for limb-threatening ischemia. Results: Twenty-nine patients were referred for arterial angiography after hemodialysis access–induced distal ischemia diagnosis and physical examination or ultrasound findings suggestive of arterial disease. In 11 patients, percutaneous transluminal angioplasty was not technically feasible. Among 18 treated patients, 83.3% had diabetes and 60% had skin ulcerations. Target arteries were radial (11), brachial (7), axillar (2), ulnar (2), and subclavian (1). Clinical success, defined as arteriovenous maintenance and wound healing/pain resolution, was observed in 12 patients (66.7%). Concomitant procedures included adjuvant banding ( n = 2) and finger amputation ( n = 1), and one reintervention was performed. No intra- or postoperative complications were reported. Conclusion: Hemodialysis access–induced distal ischemia is a serious complication of hemodialysis vascular access, with multifactorial etiology. Correct and timely diagnosis is crucial for maintaining access and limb salvage. Percutaneous transluminal angioplasty is a minimally invasive procedure that may be effective and long-lasting in carefully selected patients with ischemic complaints.